The Use of Causal Conjunction Found in “Bali Sun” E-News Articles - Ni Putu Wimarsita Putri; Putu Nur Ayomi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
Conjunction is an important element used to connect words, phrases, or clauses in a sentence. The function of conjunction is to clarify the meaning of a sentence so that it is easily understood by the writer and the reader. The aim of this research is to identify the types of causal conjunction in website of Bali Sun E-news articles. This website uploads daily news about Bali using English. Topics that are often discussed are about tourism, arts and culture, economy, social, development and others. The method used is descriptive qualitative method. That use Halliday and Hassan's (1976) theory. The result of this study is the discovery of five types of conjunctions that are stated as causal conjunctions, namely: so, therefore, because, since and as. From the five different kinds of causal conjunctions discovered, the causal conjunction so is the most widely used. The frequent use of so indicates that the cause-and0effect meaning is being made too simple in online news. Using a wider cariety of conjunctions could help make the news articles clearer and more meaningful.